Association Between Dietary Intakes and Plaque Vulnerability Measured by Optical Coherence Tomography in Patients With Coronary Heart Disease: A Mediation Analysis of Inflammatory Factors - Li, Ling; Zhao, Zhenjuan; Wang, Yini; Gao, Xueqin; Liu, Guojie; Yu, Bo; Lin, Ping (Frontiers in Nutrition, 2022)
Although studies have proven that diet has a critical role in preventing or delaying atherosclerosis and is far simpler to adjust and adhere to than other risk factors, the underlying mechanisms behind this effect remain not well comprehended. The purpose of this investigation was to determine the impact of inflammatory factors on the connection between dietary ingestion and coronary plaque fragility as measured via optical coherence tomography (OCT) in patients with coronary heart disease (CHD). This research eventually comprised 194 participants with CHD who met the inclusion and exclusion criteria. Semi-quantitative food frequency questionnaire (SQFFQ) was utilized to investigate dietary consumption status, serum levels of inflammatory biomarkers were analyzed using enzyme-linked immunosorbent assay, and OCT was employed to identify the plaque susceptibility of causative lesions in the body. Following correction for statistically meaningful possible confounders in univariate analysis, quartiles of soy and nuts, fruits and vitamin C were negatively associated with coronary plaque vulnerability. Conversely, the upper quartile group of sodium intake had 2.98 times the risk of developing vulnerable plaques compared with the most minimal quartile group. Meanwhile, we observed an inverse dose–response connection between vitamin C consumption and inflammatory biomarkers as well as plaque vulnerability. More importantly, tumor necrosis factor- α (TNF-α) and interleukin-6 (IL-6) were significant mediators of the connection between vitamin C and plaque vulnerability, suggesting that vitamin C may inhibit the atherosclerotic inflammatory process by decreasing the expression of IL-6 and TNF-α, thereby reducing the risk of vulnerable plaques. These new findings provide crucial clues to identify anti-inflammatory dietary components as effective therapeutic approaches in the management of CHD, while also providing some insights into their mechanisms of action.